2020
DOI: 10.1002/epi4.12395
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐responsive neurostimulation treatment in patients with GAD65 antibody–associated autoimmune mesial temporal lobe epilepsy

Abstract: Glutamic acid decarboxylase 65‐kilodalton isoform (GAD65) antibodies have been associated with multiple nonneurological and neurological syndromes including autoimmune epilepsy (AE). Although immunotherapy remains the cornerstone for the treatment of AE, those with GAD65 Ab‐associated AE (GAD65‐AE) remain refractory to immunotherapy and antiseizure medication (ASM). Outcomes of epilepsy surgery in this patient population have also been unsatisfactory. The role of neuromodulation therapy, particularly direct br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…48 However, some patients might be candidates for neuromodulation therapy, including responsive neurostimulation therapy, which has been approved for treating adults with medically refractory focal onset seizures arising from 1 or 2 foci. 49 The primary concern in using chronically implanted devices, including the responsive neurostimulation system, is the risk of device-related infection because some of these patients may be receiving chronic immunosuppressive treatments. Prospective multicenter trials are needed to examine the risks and efficacies of these devices in patients with drug-resistant AAE.…”
Section: Role Of Conventional Epilepsy Therapiesmentioning
confidence: 99%
“…48 However, some patients might be candidates for neuromodulation therapy, including responsive neurostimulation therapy, which has been approved for treating adults with medically refractory focal onset seizures arising from 1 or 2 foci. 49 The primary concern in using chronically implanted devices, including the responsive neurostimulation system, is the risk of device-related infection because some of these patients may be receiving chronic immunosuppressive treatments. Prospective multicenter trials are needed to examine the risks and efficacies of these devices in patients with drug-resistant AAE.…”
Section: Role Of Conventional Epilepsy Therapiesmentioning
confidence: 99%
“…More recently, neuromodulation therapy was reported in patients with AE. Feyissa et al ( 49 ) reported four patients with GAD-65 associated epilepsy treated with responsive neurostimulation (RNS) system. Three patients achieved ≥50% seizure reduction and one patient became seizure-free after RNS data-guided temporal lobectomy ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Feyissa et al ( 49 ) reported four patients with GAD-65 associated epilepsy treated with responsive neurostimulation (RNS) system. Three patients achieved ≥50% seizure reduction and one patient became seizure-free after RNS data-guided temporal lobectomy ( 49 ). In addition to immunotherapy, anti-seizure drugs, and neuromodulation, our case series adds ketogenic diet therapy to the list of potential treatments for epilepsy in patients with PE and AE.…”
Section: Discussionmentioning
confidence: 99%
“…The RNS System provides data in a naturalistic setting and may complement inpatient iEEG data and contribute to treatment decisions. Although there have been reports of neuromodulation therapy in autoimmune associated epilepsies [5] , very limited data exists on RE. To the best of our knowledge, there is only one reported case of RE with drug-resistant epilepsy treated with RNS system [6] ; La Vega-Talbott et al reported a similar case, however in a childhood-onset RE, where an 18-year-old male with a childhood-onset RE underwent successful RNS therapy after failure of several ASMs, immunotherapy and other neurostimuators.…”
Section: Discussionmentioning
confidence: 99%